2015
DOI: 10.1111/asj.12366
|View full text |Cite
|
Sign up to set email alerts
|

Selection for high and low oxygen consumption altered hepatic mitochondrial energy efficiency in mice

Abstract: Selection for high (H) and low (L) oxygen consumption (OC) as an indirect estimation of maintenance energy requirement was determined. Feed intake and body weight were measured and feed conversion ratio (FCR) of 4-8-week-old mice was calculated. Respiratory activity of hepatic mitochondria was measured at 12 weeks. Total feed intake (H: 103.74 g, L: 97.92 g, P < 0.01), daily feed intake (H: 3.70 g/day, L: 3.50 g/day, P < 0.01) and FCR (H: 18.79, L: 15.50, P < 0.01) were significantly different between lines. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(37 citation statements)
references
References 18 publications
4
33
0
Order By: Relevance
“…Furthermore, Hong et al . () confirmed that the FCR of individual feeding of the L‐line mice was significantly greater than that of H‐line mice at the 11th generation. These results confirmed that the selection for high and low OC, which was an indirect index used to measure MER, was a useful selection criterion to improve FCR.…”
Section: Discussionsupporting
confidence: 56%
“…Furthermore, Hong et al . () confirmed that the FCR of individual feeding of the L‐line mice was significantly greater than that of H‐line mice at the 11th generation. These results confirmed that the selection for high and low OC, which was an indirect index used to measure MER, was a useful selection criterion to improve FCR.…”
Section: Discussionsupporting
confidence: 56%
“…The results obtained for MH and ML were similar to those determined for high and low OC because all of them were all directly or indirectly selected based on their MER. In the presence of succinic acid substrate, the liver mitochondrial proton leak was significantly higher for the H line than the L line as previously reported (Hong et al, ). Proton leak is the mitochondrial respiration rate in the presence of an ATP synthase inhibitor and reflects state 4 respiration (Divakaruni & Brand, ).…”
Section: Discussionsupporting
confidence: 87%
“…Significant differences in FCR (Hong et al, ,) and MER (Darhan et al, ) between the H and L mouse lines were previously reported. In the present study, RFI was calculated from FI measurements in 37 mice of the 16th generation.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations